Exploitation of paddlefish Polyodon spathula (Walbaum, 1792) in the Mississippi River. (9th February 2018) - Kramer, N.; Phelps, Q.; Tripp, S.; Herzog, D.
Summary: Concern over exploitation rates of the American paddlefish Polyodon spathula from sport and commercial fisheries has increased in recent decades and the Convention on International Trade of Endangered Species is now seeking information from state agencies regarding the sustainability of commercially harvested paddlefish populations. The Missouri Department of Conservation is addressing this through the implementation of a 5‐year tagging study on exploitation of paddlefish in the Mississippi River. The first 2 years of this project found that minimal exploitation of paddlefish along Missouri's eastern border was equal to 4.01% ( SE  = 0.02). After updating previously constructed spawning potential ratio modeling completed in 2016 with the more accurate estimates of exploitation determined in this study it becomes apparent that paddlefish populations of the Mississippi River are currently at sustainable levels. However, precautionary adjustment of regulations is advised to protect paddlefish through maturation and to counteract the possibility of increased harvest intensity resulting from increased demand of domestic caviar.